Functional Outcome of Surgical Management of Comminuted Proximal Fractures of Humerus Treated with Proximal Humerus Internal Locking System (Philos) Plate - Hafiz Tayyab Irshad, Shoaib Aslam, Hafiz Muhammad Asad Aslam, Hafiz Muhammad Wasif, Muhammad Asjad Ali, Syed Salman Saqlain (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To assess the functional outcome of surgical management of comminuted proximal fractures of humerus treated with proximal humerus internal locking system (PHILOS) plate. Study Design: Descriptive study. Place and Duration: Orthopaedic Complex Bahawal Victoria Hospital Bahawalpur from 07th May 2021 to 06th November 2021. Materials & Methods: A total of 149 patients presenting with displaced proximal humerus fractures according to NEER two, three- and four-part fracture of either gender of age 18 to 60 year were included. Open fracture & Poly trauma, pathological fractures were excluded. Proximal humerus Locking plate (PHILOS) was used in each patient. Plate of appropriate size was placed over the lateral surface of humerus about 1 cm distal to upper end of greater tuberosity by an orthopedic surgeon having more than 5 years post fellowship experience. Wound close in all layers after inserting the suction drain and dressing was be applied. All postoperative rehabilitation was done under the guidance of an experienced physiotherapist. Patients encouraged to do exercises at home and called for follow-up at six weeks, three months & four months. Results: Age range in this study was from 18 to 60 years with mean age of 37.15 ± 7.41 years. Majority of the patients 79 (59.73%) were between 18 to 40 years of age. Out of 149 patients, 99 (66.44%) were males and 50 (33.56%) were females with male to female ratio of 2:1. In this study, the excellent functional outcome was seen in 71 (47.65%) patients, very good in 14 (9.40%), good in 40 (26.85%) patients, fair in 15 (10.07%) and poor outcome in 09 (6.04%) patients. Conclusion: This study concluded that excellent functional outcome of surgical management of comminuted proximal fractures of humerus treated with proximal humerus interlocking system (PHILOS) plate is very high. Keywords: proximal fractures of humerus, proximal humerus interlocking system, outcome.